From Pulsation to Sensation: Virtuosity and Modernism in Ligeti's First and Ninth Piano Études. Issue 3 (4th July 2019) - Bauer, Amy
Abstract : Nineteenth century musical virtuosity revived ideals concerning heroic agency via an artist-hero whose performance functioned rhetorically, to excite audiences attuned to progressive ideals. I argue that the virtuoso as 'ideological architect and symbol' [Palmer 1998. "Virtuosity as Rhetoric: Agency and Transformation in Paganini's Mastery of the Violin." Quarterly Journal of Speech 84: 341–357, 353] lives on in late modernism in a conflicted repertoire that both redoubles and rejects virtuosity, as in Ligeti's Études pour Piano (1985–2001). In 'Désordre' and 'Vertige' (the first and ninth études), this critique plays out aurally as a conflict between a surface virtuosic rhetoric and its subversion. But the evolution of reflexive codes that establish critical distance from those conventions can also be traced through letters and sketches housed at the Paul Sacher Stiftung. Like Edward Said's late modern hero, Ligeti's études and their reception history unite humanist sympathy towards tradition with critique of a contemporary culture balanced precariously on masterworks and performances of the past.